Aging Masculinities and Long-Term Residential Care in Jon Hassler’s 'Simon’s Night' (1979) - Mariana Batista da Cruz (Anglo Saxonica)
The present article is built on the premise that aging is a gendered experience. It will add to recent scholarship in the field of aging studies, which focuses on how age plays into the formation of masculine identities. Embracing the notion that models of masculinities are accomplished in social practice, this study will analyse how the older male characters in Jon Hassler’s 1979 novel Simon’s Night negotiate their identities following the transition to long-term residential care. Emphasis will be placed on the efforts of the novel’s protagonist Simon to try and counter the process of social ‘degendering’, which accompanies his aging experience. One of these strategies consists of escaping the nursing home to recover both his lost car and his lost autonomy, a decision that reflects the novel’s compliance with positive aging theories. The article will argue that this journey of emancipation constitutes a missed opportunity: in returning to the activities and principles that defined his identity in middle age, Simon does not contemplate the possibility of incorporating age-related changes into a more fluid sense of self that disrupts the rigidity of traditional masculine ideals. On the contrary, his character arc endorses progress narratives of aging, reflecting culturally pervasive beliefs in the righteousness of activity and independence as solutions for ‘aging well’.